EFFECTIVENESS OF THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL OF TAI TYPE WITH CONTEXTUAL-SCIENTIFIC APPROACH IN MATHEMATICS LEARNING TO CLASS VII STUDENTS - Khusaimah, Nurul (Universitas Negeri Makassar, 2018)
The research is experiment which aims to describe Cooperative Learning Model of TAI Type with Contextual-Scientific Approach in Mathematics Learning in Social Arithmetic and Comparison material to class VII Students at SMPN 2 Bontonompo Selatan. The effectiveness description is based on (1) student’s learning results, (2) student’s activities, and (3) student’s response. The populations of the research were all of the students of class VII at SMPN 2 Bontonompo Selatan and the samples were the students of class VII.A as the experiment class taught by using cooperative Learning Model of TAI Type with Contextual-Scientific approach chosen by using simple random sampling technique. The data collection consisted of learning results, student’s activities in learning, and student’s responses on learning devices. Instrument used are test of learning results, observation sheets of student’s activities in learning and questionnaires of student’s responses on learning devices. The data of the students’ activities were analyzed by using descriptive analysis while the data of mathematics learning results and students’ responses were analyzed by using descriptive and inferential analysis. The results of descriptive and inferential analysis reveal that the implementation of Cooperative Learning Model of TAI Type with Contextual-Scientific approach is effective to be implemented in mathematics learning in social arithmetic and Comparison material to class VII students at SMPN 2 Bontonompo Selatan based on the aspect: (a) the average score of Mathematics learning results in posttest is bigger than 69.9 (Minimum Completeness Criteria= 70) which is 79.9 in High category, the average score of normalized gain is bigger than 0.29 (medium category) which is 0.73 in High classification category, and the proportion of the students’ learning completeness is more than 84%; (b) the average score of student’s learning activities from the first until the fifth meeting are more than 2.49 (minimum fairly active category) which is 3.15 in fairly active category, and (c) the average score of students’ response is bigger than 2.49 (minimum tend to be positive category) which is 3.64 in positive category. The conclusion of the research is Cooperative Learning Model of TAI Type with Contextual-Scientific approach is effective to be implemented in mathematics learning in Social arithmetic and Comparison material to class VII students at SMPN 2 Bontonompo Selatan in Gowa District.